The interface between the trade and climate change regimes: Scoping the issues - Patrick Low; Gabrielle Marceau; Julia Reinaud (World Trade Organization (WTO), 2011)
As governments increasingly adopt policies to reduce greenhouse gas emissions, concern has grown on two fronts. First, carbon leakage can occur when mitigation policies are not the same across countries and producers seek to locate in jurisdictions where production costs are least affected by emission constraints. The risk of carbon leakage raises questions about the efficacy of climate change policies in a global sense. Secondly, it is precisely the cost-related consequences of differential mitigation policies that feed industry concerns about competitiveness. We thus have a link between environmental and competitiveness perspectives that fuses climate change and trade regimes in potentially problematic ways as governments contemplate trade actions to manage the environmental and/or competitiveness consequences of differential climate change policies. On the trade side of this relationship, we have the reality that the GATT/WTO rules were not originally drafted to accommodate climate change policies and concerns. The purpose of this paper is to analyze the relevance of certain WTO rules to the interface between climate change and trade, focusing in particular on border measures, technical regulations on trade, standards and labelling, and subsidies and countervailing duties. It concludes that in the absence of clear international understandings on how to manage the climate change and trade interface, we run the risk of a clash that compromises the effectiveness of climate change policies as well as the potential gains from specialization through trade.
Keywords: F13; F18; K33; Q54; 330; border adjustments; carbon leakage; climate change; competitiveness; GATT/WTO; standards; trade; Klimaveränderung; Klimaschutz; WTO-Regeln